Etanercept-induced myositis: do we have to stop it? A surprising outcome. (11th January 2016) - Tariq, Hassan; Ayesha, Bibi; Weidenheim, Karen; Franchin, Giovanni
Abstract : We discuss a case of a 47-year-old man who presented with progressive proximal muscle weakness of the upper and lower extremities and unstable gait. He had been on etanercept for 6 months for severe psoriasis and psoriatic arthritis with good control of his disease. Serum creatine kinase (CK) level was found to be 5666 U/L and muscle biopsy showed a marked inflammatory myopathic process likely secondary to etanercept. He was started on high-dose steroids and advised to discontinue etanercept. Despite our recommendation, he never stopped using etanercept due to fear of a psoriasis flare. Three months later, he had significant improvement of clinical symptoms, normalised serum CK levels and discontinued prednisone.